EFEKTIVITAS KEKUATAN STRUKTUR KOLOM AKIBAT PERUBAHAN FUNGSI GEDUNG PADA PROYEK MAGNA ONE SURABAYA TERHADAP BEBAN GEMPA - Hernita, Faradiba Dwi (Jurnal Vokasi Teknik Sipil, 2023)
Changes in the function of the Magna One Surabaya Building, originally Full Office to Mixed Use to meet the market share needs for vertical housing in the West Surabaya area. This resulted in a change in the dimensions and quality of the concrete in the column structure of the building. This research was conducted to compare the column structure deviation of the two building models due to changes in building function. The research method uses SAP 2000 software and refers to SNI 1726:2019. Results in this study, it was found that the mass of the Mixed Use structure is greater than the Full Office structure with a percentage value increase of 0.3% in structural mass due to the addition of column reinforcement in the form of extra main reinforcement, extra stirrup reinforcement, and the addition of hooks to the 16th to 19th floor structural columns. Axial force the Mixed Use structure is 17484.71 kN, the maximum deviation value is 41.2 mm in the safe category not exceeding the permit delta, the Base Shear Reaction value is greater in the Mixed Use structure, for the Mixed Use period it is 4.24 seconds which is 6.19% more smaller than the period of the Full Office structure. The structure period that works on the SAP 2000 program is still within safe limits of no more than 5.425 seconds so that the Mixed Use structure is more effective.